(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Breast measurement presents a complex challenge in the design of sports bras, particularly for adolescent girls whose bodies are rapidly changing. This study aimed to explore breast anthropometry among adolescents. A survey involving 23 girls aged 10 to 14 assessed their understanding of bra-related problems. In comparison, a wear trial with 7 girls sized 30AA to 32A evaluated their preferences through five bra conditions, 3D scanning and questionnaires. The study revealed a significant knowledge gap, with only 8.7% having had a bra fitting and less than half knowing how to determine their bra size. Notably, the upper bust measurement was significantly correlated with the level of “coolness” (r=−0.395 and p = 0.038), and the under bust measurement was correlated with the level of “comfort” (r = −0.441 and p = 0.019). The findings suggest a need for breathable fabrics in the upper bust while a preference for a stretchable underband to accommodate body growth. These results highlight the need to design sports bras tailored to the unique needs of adolescent girls, providing designers with critical insights into the necessary features and dimensions for optimal comfort during physical activity.